2021
DOI: 10.1097/md.0000000000027158
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications observed with robotic versus laparoscopic surgery for the treatment of rectal cancer

Abstract: Background: This is an updated meta-analysis comparing the postoperative complications observed with robotic versus laparoscopic surgery (LS) for the treatment of rectal cancer. Methods: Cochrane central, MEDLNE (Medical Literature Analysis and Retrieval System Online), EMBASE (Excerpta Medica dataBASE), Google Scholar, Web of Science and http://www.ClinicalTrials.gov were searched for studies (published after the year 2015), comparing robotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…The robotic surgical systems for the treatment of colorectal cancer were introduced into this hospital in 2020, but only a minority of patients have been treated with robotic surgery because of its high cost. Previous studies have shown that there are no significant differences between laparoscopic and robotic approaches to PPOI and perioperative mortality [ 32 , 33 ]. Therefore, we combined laparoscopic and robotic surgery into one group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The robotic surgical systems for the treatment of colorectal cancer were introduced into this hospital in 2020, but only a minority of patients have been treated with robotic surgery because of its high cost. Previous studies have shown that there are no significant differences between laparoscopic and robotic approaches to PPOI and perioperative mortality [ 32 , 33 ]. Therefore, we combined laparoscopic and robotic surgery into one group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a broader surgical context, meta‐analyses in gastric cancer surgeries comparing robotic and open approaches have found no significant difference in the rate of wound infections between the two methods. Similarly, research in rectal cancer surgeries comparing robotic and laparoscopic approaches has shown no significant differences in overall complications, including wound complications 5 . These findings are crucial as they offer a broader perspective on the efficacy of robotic surgery across different types of cancer surgeries.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, research in rectal cancer surgeries comparing robotic and laparoscopic approaches has shown no significant differences in overall complications, including wound complications. 5 These findings are crucial as they offer a broader perspective on the efficacy of robotic surgery across different types of cancer surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…The Evolution of Research in Health Science Robotic surgery in patients with colorectal cancer: Techniques and benefits -Integrative review nervous structures. 12,13 In addition, robotic surgery eliminates physiological tremors, offers greater ergonomic comfort and reduces surgeon fatigue 13,14,15,16,17,18,19,20 .The robotic system also demonstrates ambidextrous ability during the surgical procedure, providing greater precision and allowing the execution of fine and precise movements, thanks to its advanced computer interface.In addition, there is preservation of the patient's voiding and sexual function, as this technique protects the superior and inferior hypogastric nerve plexus, as well as the pelvic nerve. 21,15 Similarly, in their randomized clinical trial, Chang et al 22 compared robotic surgery with open surgery for the simultaneous resection of rectal cancer and liver metastases, in which it was noted that 76 patients (44.4%) had surgical complications: 27 (31.4%) in the robotic group and 49 (57.6%) in the open group.…”
Section: Historical Evolution: From Traditional Surgical Practice To ...mentioning
confidence: 99%